2019
DOI: 10.5194/acp-2019-190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predominance of Secondary Organic Aerosol to Particle-bound Reactive Oxygen Species Activity in Fine Ambient Aerosol

Abstract: <p><strong>Abstract.</strong> Reactive oxygen species (ROS) are believed to contribute to the adverse health effects of aerosols. This may happen by inhaled particle-bound (exogenic) ROS (PB-ROS) or by ROS formed within the respiratory tract by certain aerosol components (endogenic ROS). We investigated the chemical composition of aerosols and their exogenic ROS content at the two contrasting locations Beijing (China) and Bern (Switzerland). We apportioned the ambient … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Therefore, SO 2 reactions have a strong impact on atmospheric fate of peroxides and aging of SOA. Furthermore, it has been shown that both laboratory-generated and ambient SOA are a significant source of particle-bound reactive oxygen species (ROS) including H 2 O 2 , OH, and organic radicals, ,,, which are believed to play a critical role in adverse health effects of atmospheric particles . Since organic peroxides are a potentially important source of these ROS, the alternation in its atmospheric fate by SO 2 reactions may significantly influence the health effect of SOA particles.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SO 2 reactions have a strong impact on atmospheric fate of peroxides and aging of SOA. Furthermore, it has been shown that both laboratory-generated and ambient SOA are a significant source of particle-bound reactive oxygen species (ROS) including H 2 O 2 , OH, and organic radicals, ,,, which are believed to play a critical role in adverse health effects of atmospheric particles . Since organic peroxides are a potentially important source of these ROS, the alternation in its atmospheric fate by SO 2 reactions may significantly influence the health effect of SOA particles.…”
Section: Resultsmentioning
confidence: 99%